A BIG DATA AND IT’S SECURITY CHALLENGE IN DIGITAL MEDIA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research work discuss about the big data and related problem. In the currentgeneration big data play’s an important role in various data mining application. This researchwork discuss the various field in which apply big data application. There are many criticalissues and challenges face in the big data. Big Data Duplication is one of the challengingproblem between researchers. In the last decade the growth of big data exponentiation,Terabytes, Petabyte, Exabyte, Zettabyte bytes data generated in every day in a single stockmarket research application. In this process huge amount of decapitate data also generated inTerabytes as well as Petabytes. Similar that social media application generated large amountof duplicate information. In this research work focus on different problems and hurdles of bigdata and its related issues.However, encrypted information introduce new challenges for cloudinformation de-duplication that becomes crucial for giant information storage and process incloud. De-duplication schemes cannot work on encrypted information. Existing solutions ofencrypted information de-duplication suffer from security weakness. They cannot flexiblysupport information access management [13] and revocation. Therefore, few of them is prontodeployed in observe. During this paper, we propose a theme to de-duplicate encryptedinformation hold on in cloud supported possession challenge and proxy re-encryption. Itintegrates cloud information de-duplication with access management.